PERAN MAHASISWA PGSD DALAM PENGELOLAAN TATA USAHA DI SMA NEGERI 1 CIBADAK - Diki Firmansyah; Any Elvia Jakfar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This service activity aims to increase the efficiency and effectiveness of administrative management at SMA Negeri 1 Cibadak through direct involvement of students from the Primary School Teacher Education Study Program (PGSD). For five months, students participate in various administrative activities, including archiving documents, managing student data, preparing financial reports, and updating school information systems. Qualitative research methods are used with data collection techniques through interviews, observation and documentation. The results of the activity show an increase in the quality of school administration services, marked by a more structured filing system, more accurate student data management, as well as increasing the competency of administrative staff through short training. This activity also provides practical experience for students in the field of educational management. However, challenges such as time constraints and adaptation to existing administrative systems need to be taken into account when planning similar programs in the future. Overall, collaboration between PGSD students and administrative staff makes a positive contribution to improving the quality of school administrative services. Keywords: PGSD Students, School Administration, Administrative Management